Ecological Survey of the Peridomestic Sand Flies of an Endemic Focus of Zoonotic Cutaneous Leishmaniasis in the South-East of Morocco. (10th November 2022) - Al-Koleeby, Zalalham; El Aboudi, Ahmed; Van Bortel, Wim; Cloots, Kristien; Benkirane, Raja; Faraj, Chafika; Talbi, Fatima Zahra
Abstract : Leishmaniasis is a parasitosis caused by parasites of the genus Leishmania and is transmitted by Phlebotominae sand flies. An entomological survey was carried out in different localities of Zagora Province. Our work allowed us to establish an inventory of sand flies to study potential vectors of leishmaniasis and to compare the composition and the specific abundance of different endemic stations. The sand flies were collected using CDC miniature light traps during the month of July 2019 in the ten studied villages. The results indicate the presence of thirteen species, belonging to the genera Phlebotomus and Sergentomyia . Phlebotomus papatasi was the predominant species (46.65%) followed by Ph . alexandri (17%), Ph . longicuspis (11.55%), Ph . bergeroti (1.53%) and Ph . sergenti (1.27%). Phlebotomus kazeruni (0.03%) was rare, and only one female was captured in Ifred. Sergentomyia schwetzi (8.69%) was the most prevalent species in the Sergentomyia genus followed closely by Se . fallax (6.84%). Sergentomyia africana was present with a proportion of (3.86%) followed by Se . clydei (1.96%). Sergentomyia dreifussi (0.46%), Se . antennata (0.08%), and Se . minuta (0.08%) were very limited. Phlebotomus papatasi, Ph . alexandri, Ph . bergeroti, Ph . longicuspis, Ph . sergenti, Se . schwetzi, Se . clydei, and Se . fallax are constant species, being present at least in 50% of the stations (occurrence> 50%). Common species (25%–49%) were Se . minuta and Se . africana and rare species were Ph . kazeruni and Se . antennata with a very limited distribution (occurrence <12%). The greatest species richness was found in Ksar Mougni and Ifred with the occurrence of 11 species, but overall, it was high (>9 species) in most of the villages. The Shannon–Wiener index was high ( H ′ > 1) in eight localities (Ksar Mougni, Tassaouante, Bleida, ZaouiteLeftah, Ifred, Timarighine, Ait Oulahyane, and Ait Ali Ouhassou). The high value of this index is in favor of the ZaouiteLeftah locality (Shannon–Wiener index = 1.679) which is explained by the presence of a stand dominated by Ph . papatasi . In order to avoid exposure to infections, a good epidemiological surveillance and vector with rodent control measures must be well maintained. Awareness campaigns are also required and must be conducted for better knowledge of the disease.